Pengaruh Disiplin Dan Lingkungan Kerja Terhadap Kinerja Karyawan Divisi Warehouse Pada PT Eka Mas Republik Tangerang - Lulu Atun Fitriyah; Nopi Oktavianti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this study was to determine the Influence of Discipline and Work Environment on Employee Performance in the Warehouse Division at PT Eka Mas Republik Tangerang. The method used is quantitative descriptive. The results of this study are that discipline has a significant effect on employee performance with the regression equation Y = 24.730 + 0.372X1, the correlation coefficient value of 0.463 means that the two variables have a moderate level of relationship with a determination coefficient value of 21.5% and the hypothesis test obtained t count> t table or (3.982> 2.001) this is reinforced by a probability significance of 0.000 t table or (3.352> 2.001) this is reinforced by the probability significance of 0.001 F table or (7.903 > 2.77). This is also supported by the ρ value < 0.050). The correlation coefficient value obtained is 0.466, meaning that the work discipline variable (X1) and work environment (X2) have a moderate level of relationship with a determination coefficient value of 21.7% while the remaining 78.3% is influenced by other factors. The hypothesis test obtained a calculated F value > F table or (7.903 > 2.77). This is also supported by the ρ value < 0.050).